Implementasi Strategi Media Sosial Marketing pada UMKM Bubur Ayam Sari Rasa - Monica Nanda; Andina Fasha (Universitas Internasional Batam, 2025)
This community engagement project was carried out to address the low digital marketing capabilities of MSME Bubur Ayam Sari Rasa, which previously relied only on traditional promotion without a structured social media strategy. The MSME did not have a visual identity, did not maintain active social media accounts, and had limited digital literacy, all of which affected its promotional reach. The methods included interviews with the business owner to understand operational needs, field observations to examine existing promotional practices, and the design and implementation of strategies such as logo creation, Instagram and TikTok management, content calendar development, photo and video production, and social media training. The results showed significant improvements, including a more professional social media appearance, consistent posting, and increased TikTok insights within 60 days, reflected in higher views, interactions, and audience reach. The findings provide insight that visual content, storytelling, and consistent publication strongly influence MSME development in the digital era. Recommendations for future projects include advanced training on paid advertising, algorithm optimization, and creative content development to support the sustainability of digital promotion.